'Abortion jurisprudence' at Strasbourg: deferential, avoidant and normatively neutral?. (1st May 2013) - Fenwick, Daniel
<x xml:space="preserve">Abstract</x> This paper evaluates the role being adopted by the European Court of Human Rights when confronted with claims arising from the extreme restriction of access to abortion services in certain Member States. It will be argued that in response to such claims the Court has been prepared to find that the suffering of the applicants can be captured as forms of rights violation, but it has sought to avoid taking a stance as to foetal life, leading it to adopt a highly deferential approach and to avoid the substantive issues at stake, of protection for female reproductive health, dignity and autonomy, in favour of focusing mainly on procedural ones. Having considered such issues as the missing gender‐based aspects of the abortion jurisprudence, this paper concludes that its restrained and largely procedural stance has enabled the Court to provide some limited protection for women, on healthcare grounds, but that the opportunity to recognise that highly restrictive abortion regimes systematically and persistently create especially invidious discrimination based on gender has so far been missed.